Identity leadership: Managing perceptions of conflict for collective action. (2019) - Pärnamets, Philip; Reinero, Diego A.; Pereira, Andrea; Van Bavel, Jay J.
Abstract: We argue that how players perceive the attack-defense game might matter far more than its actual underlying structure in determining the outcomes of intergroup conflict. Leaders can use various tactics to dynamically modify these perceptions, from collective victimization to the distortion of the perceived payoffs, with some followers being more receptive than others to such leadership tactics.